Cuckoo as indicator of high functional diversity of bird communities: A new paradigm for biodiversity surrogacy. (January 2017) - Morelli, Federico; Møller, Anders Pape; Nelson, Emma; Benedetti, Yanina; Tichit, Muriel; Šímová, Petra; Jerzak, Leszek; Moretti, Marco; Tryjanowski, Piotr
Highlights: Occurrence of European cuckoo was tested as surrogate for biodiversity. Taxonomic diversity (TD) and functional diversity (FRic, FEve, FDiv) were estimated. Average evolutionary distinctiveness (ED) was estimated in each bird community. Cuckoo occurrence predicts TD, FRic, and FEve but not ED of bird communities. The cuckoo offers a cost-effective conservation tool, useful for citizen science. Abstract: We tested the hypothesis that the cuckoo may serve as an effective surrogate for different aspects of biodiversity. Six different measures of biodiversity were estimated for these three bird communities: (a) taxonomic diversity, (b) host species richness, (c) functional richness, (d) functional evenness, (e) functional divergence, and (f) evolutionary distinctiveness. Mixed models were used for studying the patterns of occurrence of the cuckoo in relation to environmental variables and biodiversity measures. The presence of the cuckoo was positively correlated with high values of taxonomic diversity, functional richness and functional evenness, but not with functional divergence or evolutionary distinctiveness of bird communities. We demonstrate that host species represent different levels of functional diversity in bird communities, because they are broadly distributed and occupy many niches for breeding and feeding. The implications for conservation are many: Hotspots determined by the occurrence of the cuckoo are areas with higher functional richness and evenness, also indicating high potential resilience. If host species are functionally diversified, the bird community provides higher resilience to any eventual catastrophic events. Finally, we underline how the cuckoo is a charismatic species, easy to monitor and adequate for citizen science, providing new information on the paradigm of surrogacy in ecology.